EFFECTIVENESS AND SAFETY OF PIMECROLIMUS IN TREATMENT OF ATOPIC DERMATITIS IN CHILDREN AND ADOLESCENTS - K.N. Monakhov; S.A. Ochelenko ("Paediatrician" Publishers LLC, 2008)
The results of treatment of 57 patients with atopic dermatitis (ATD) in age 7-18 years old with elidel cream are described. Cream was drifted on facial skin 2 times daily. Apparent effect was marked on 7-14 day. There was no any case of serious adverse events. Thus, taking to account safety and effectiveness profile, pimecrolimus can be used as a medication of first line of therapy in treatment of ATD, while lesion is located on sensitive sectors of skin.Key words: children, atopic dermatitis, pimecrolimus.